Design and Simulation of VPN based Private Network with Regulatory Compliance and Economic Feasibility Analysis in Government WAN Infrastructure - Dara Kusumawati Ramadani Yasir; Rendy Munadi; Helni Mutiarsih Jumhur (Dinasti Publisher, 2025)
The increasing reliance on private networks in modern enterprise highlights the need for efficient and reliable network performance to support business operations. WAN is a backbone for connecting branch offices, enabling data exchange and coordination across geographically dispersed locations. However, maintaining optimal performance amidst growing traffic demands, latency issues, and packet loss remains a significant challenge. This study focuses on developing VPN technol ogy integrated with QoS management to enhance network reliability, scalability, and efficiency in WAN environments. By employing a simulated network emulator, the research evaluates key performance indicators such as latency, bandwidth utilization, and packet loss under varying network conditions. The study further integrates technoeconomic analysis to assess the feasibility of the proposed solution, considering capital expenditures, operational costs, and the financial viability of the implementation. Regulatory compliance is also considered, with a focus on ensuring that the proposed framework aligns with national and international laws and policies, particularly those governing private networks and WAN operations. The results aim to provide enterprises with a strategic approach to optimizing VPN and WAN performance while balancing operational demands, cost efficiency, and legal adherence. This comprehensive framework is expected to contribute to the development of sustainable network solutions for modern enterprise, ensuring improved productivity and business continuity in an increasingly connected digital landscape.